Stevens-Johnson syndrome with overlapping features of DRESS syndrome: A report of two cases - Laura D Chin; Michael L MacGillivary; Kerri S Purdy; Carly Kirshen (SAGE Open Medical Case Reports)
Stevens-Johnson syndrome and drug reaction with eosinophilia and systemic symptoms are severe cutaneous adverse reactions to drugs that are generally considered distinct entities. In addition to identifying the offending medication, distinguishing between these diagnoses is important, as they have differing treatment regimens and prognoses. Distinction between severe cutaneous adverse reactions, particularly in the early stages of disease, can be difficult, and overlapping conditions have been reported in the literature. We present two cases of severe cutaneous adverse reaction, one following initiation of carbamazepine and the other lamotrigine, with extensive mucosal involvement and epidermal detachment, initially diagnosed as Stevens-Johnson syndrome. Despite the use of cyclosporine and repeated doses of etanercept, both cases evolved to have significant edema of the face and extremities, palmar and plantar involvement, and rapid response to systemic corticosteroids, which is more in-keeping with drug reaction with eosinophilia and systemic symptoms. We aim to help clinicians gain awareness of Stevens-Johnson syndrome/drug reaction with eosinophilia and systemic symptoms overlap which may aid diagnosis and guide treatment.